Protective Effect of Rosmarinic Acid on Endotoxin-Induced Neuronal Damage Through Modulating GRP78/PERK/MANF Pathway - Li Q; Zheng JW; Wang ZY; Liao SP; Zhu L; Wang X; Wan LH (Drug Design, Development and Therapy)
Qian Li,1,* Jing-Wen Zheng,1,* Zi-Yao Wang,1 Shi-Ping Liao,2 Ling Zhu,1 Xia Wang,3,* Li-Hong Wan1,4,* 1Department of Pharmacology, West China School of Basic Medical Sciences & Forensic Medicine, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 2Functional Laboratory, West China School of Basic Medical Sciences & Forensic Medicine, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 3Department of Laboratory Medicine, West China Second University Hospital, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 4NHC Key Laboratory of Chronobiology (Sichuan University), West China School of Basic Medical Sciences & Forensic Medicine, West China Second University Hospital, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li-Hong Wan, Department of Pharmacology, West China School of Basic Medical Sciences & Forensic Medicine, Sichuan University, Chengdu, 3-17 Renmin South Road, Sichuan, 610041, People’s Republic of China, Tel +86-28-85501278, Email wanlihong1976@sina.com Xia Wang, Department of Laboratory Medicine, West China Second University Hospital, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China, Email 80832491@qq.comObjective: Neuronal damage is criminal to cognitive dysfunction, closely related to endoplasmic reticulum stress (ERS). However, due to the pathogenesis of endotoxin-induced long-term cognitive dysfunction is not fully clarified, there is still a lack of effective treatment. This study was conducted to explore the protective effects and mechanism of rosmarinic acid (RA) against ERS in endotoxin-induced cognitive dysfunction in mice and neuronal injury in cells.Methods: The efficacy of RA was evaluated using an endotoxin-induced cognitive dysfunction mice model and an in vitro neuronal injury model. Brain injury was assessed using behavioral tests and hematoxylin and eosin (HE) staining. Western blotting and Immunohistochemistry (IHC) were performed to determine NeuN, GRP78, PERK, ATF6, IRE1α, and MANF expression levels. Molecular docking was used to assess the associated mechanisms.Results: Behavioral tests indicated that 20 and 40 mg/kg RA significantly improve endotoxin-induced cognitive dysfunction without dose differences. Histological analysis revealed no significant alterations in the number, morphology, and arrangement of neurons in the hippocampus and amygdala. However, 40 mg/kg RA treatment significantly decreased the hippocampal level of PERK protein and increased MANF in CA1 and DG in mice. Furthermore, our data showed that 120 μM RA pretreatment significantly inhibited LPS-conditioned culture-induced GRP78, PERK, and MANF upregulation in vitro. Finally, molecular docking studies suggested that RA could directly interact with GRP78, PERK, and IRE1, but not with MANF.Conclusion: RA plays a protective role in improving cognitive function against endotoxemia-associated encephalopathy in mice via inhibiting the GRP78/PERK/MANF pathway.Keywords: Rosmarinic acid, endotoxin, neuronal damage, GRP78/PERK/MANF pathway